ANALISIS RESIKO PRODUKSI DAN PENDAPATAN USAHATANI PADI ORGANIK DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - ainul mardliyah (STIPER Dharma Wacana Metro, 2019)
The objective of this research to analyze the risk of production and income of organic rice farming in the District of Seputih Raman Central Lampung Regency. The research method used is survey method, which was conducted in Rejo Asri Village Seputih Raman District, Central Lampung Regency. The study was conducted in January to March 2019.Sampling in this study was carried out by census with the number of samples were 20 farmers in farmer groups who participated in organic rice cultivation in Rejo Asri Village, Seputih Raman District, Central Lampung Regency. The analysis used the coefficient of variation (CV).The results of the study and discussion it can be concluded that: production risk and risk of income in organic rice farming in Kampung Rejo AsriDistrict of Seputih Raman Central Lampung Regency has a high risk with a coefficient of variation for production risk of 0.566 and risk of income of 0.576.